2017
DOI: 10.1148/rg.2017170006
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease in Children Made Easier…Well, Almost

Abstract: Interstitial lung disease (ILD) in pediatric patients is different from that in adults, with a vast array of pathologic conditions unique to childhood, varied modes of presentation, and a different range of radiologic appearances. Although rare, childhood ILD (chILD) is associated with significant morbidity and mortality, most notably in conditions of disordered surfactant function, with respiratory failure in 100% of neonates with surfactant protein B dysfunction and 100% mortality without lung transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 73 publications
2
39
0
9
Order By: Relevance
“…The pulmonary growth abnormality associated with FLNA deficiency consists of multilobar overinflation predominantly affecting the upper and lower lobes, with coarse septal thickening and varying lower lobe atelectasis with pruning of the peripheral pulmonary vasculature [27]. The role of FLNA in the development of lung disease is still not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary growth abnormality associated with FLNA deficiency consists of multilobar overinflation predominantly affecting the upper and lower lobes, with coarse septal thickening and varying lower lobe atelectasis with pruning of the peripheral pulmonary vasculature [27]. The role of FLNA in the development of lung disease is still not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In a large series of lung biopsies, it has been demonstrated that in children, 2 to 18 years of age, the pathologic spectrum of DLD overlaps with that seen in adults with some exceptions, but differs from that detected in infants . The disorders of the later childhood are subdivided into disorders of the normal host, disorders related to systemic disease processes, and disorders related to immunodeficiency …”
Section: Introductionmentioning
confidence: 86%
“…9 The disorders of the later childhood are subdivided into disorders of the normal host, disorders related to systemic disease processes, and disorders related to immunodeficiency. 10 Among disorders related to systemic diseases, NF-1 lung involvement has never been investigated in children.…”
mentioning
confidence: 99%
“…Chest radiograph, albeit being the starting point, is highly non-specific with a limited sensitivity. CT is the gold standard in the work-up of interstitial lung disease in pediatric patients, since it provides information about the extent and distribution of parenchymal disorders (pattern recognition), contributing in estimating the severity of the disease, the response to treatment and the prognosis, as well as indicating a site for biopsy [2,3,10]. Occasionally, abnormalities affecting other systems (eg, cardiovascular) may be diagnosed.…”
Section: Terminology and Classificationmentioning
confidence: 99%
“…Spontaneous pneumothorax is a potential complication. An enlarged thymus may also be seen with intrathymic calcification-cavitation being characteristic of the disease, rendering lung biopsy unnecessary (Figure 9) [7,10,13].…”
Section: Langerhans Cell Histiocytosismentioning
confidence: 99%